2014
DOI: 10.1159/000369257
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Methods Feasibility Trial of Protein Kinase C Iota Inhibition with Auranofin in Asymptomatic Ovarian Cancer Patients

Abstract: Purpose: This trial was undertaken (1) to determine the feasibility of enrolling asymptomatic ovarian cancer patients with CA-125 elevation in a trial with the protein kinase C iota (PKCι) inhibitor auranofin and (2) to understand patients' perceptions of CA-125 monitoring. Methods: Asymptomatic ovarian cancer patients with CA-125 elevation received 3 mg auranofin orally twice per day and were evaluated. The patients participated in interviews about CA-125 monitoring. Results: Ten patients were enrolled in sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 9 publications
0
25
0
2
Order By: Relevance
“…In this regard, we have observed preliminary clinical activity of ANF in ovarian cancer patients in a maintenance setting. 37 Our current results indicate that ANF may be of particular utility in the ~80% of OSC tumors harboring PRKCI CNGs, elevated PKCι, and activation of PKCι-AMOT-YAP1 signaling.…”
Section: Discussionmentioning
confidence: 56%
“…In this regard, we have observed preliminary clinical activity of ANF in ovarian cancer patients in a maintenance setting. 37 Our current results indicate that ANF may be of particular utility in the ~80% of OSC tumors harboring PRKCI CNGs, elevated PKCι, and activation of PKCι-AMOT-YAP1 signaling.…”
Section: Discussionmentioning
confidence: 56%
“…Interestingly, response to ATM and ANF correlates directly with PRKCI CNG and elevated PKCι expression, indicating that 3q26 CNG-driven tumors may be particularly sensitive to PKCι inhibitor therapy (Regala et al, 2008). Our initial clinical experience with these agents has demonstrated proof of principle for PKCι inhibition using ATM or ANF as a viable therapeutic approach in both LSCC and ovarian serous cancer, tumor types exhibiting frequent 3q26 CNGs (Jatoi et al, 2014, Mansfield et al, 2013). These agents were well tolerated in the oncology setting at concentrations that exhibit effective anti-tumor activity, and these agents have shown promising initial indications of clinical activity in heavily pre-treated patients with advanced disease.…”
Section: Resultsmentioning
confidence: 99%
“…GSI inhibitors of NOTCH exhibit potent anti-tumor activity in glioma (Fan et al, 2010; Fan et al, 2006), lung (Konishi et al, 2007), and ovarian cancers (Groeneweg et al, 2014a; Groeneweg et al, 2014b) and the potent GSI PF-03084014 has shown clinical promise in advanced cancer patients (Messersmith et al, 2015). The anti-rheumatoid gold salts ATM and ANF selectively inhibit PKCι signaling and block growth of lung (Erdogan et al, 2006; Fields et al, 2007; Regala et al, 2008; Stallings-Mann et al, 2006), pancreatic (Butler et al, 2015; Scotti et al, 2012) and ovarian (Wang et al, 2013) tumors in vitro and in vivo , and two clinical studies have demonstrated proof-of-principle for PKCι inhibitor-based therapy with ATM (Mansfield et al, 2013) and ANF (Jatoi et al, 2014). Our finding that GSI and ANF exhibit highly synergistic anti-tumor activity suggests a novel therapeutic approach to treat KRAS LADC, a tumor sub-type for which there is a dire need for effective targeted therapeutics.…”
Section: Discussionmentioning
confidence: 99%